2004
DOI: 10.1074/jbc.m310771200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Substrate Specificity and Function of Glucodextranase

Abstract: A glucodextranase (iGDase) from Arthrobacter globiformis I42 hydrolyzes ␣-1,6-glucosidic linkages of dextran from the non-reducing end to produce ␤-D-glucose via an inverting reaction mechanism and classified into the glycoside hydrolase family 15 (GH15). Here we cloned the iGDase gene and determined the crystal structures of iGDase of the unliganded form and the complex with acarbose at 2.42-Å resolution. The structure of iGDase is composed of four domains N, A, B, and C. Domain A forms an (␣/␣) 6 -barrel str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…The GH-15 thread coverage of ␤ is indicated in a two-color scheme, with blue and gray representing, respectively, the (␣/␣) 6 -barrel fold for the catalytic domain (A) and a mixed 2°structure corresponding to the B and C domains found in bacterial and archaeal glucoamy- lases and glucodextranases (61). The protein structurally closest to the best model of this region is Anthrobacter globiformus glucodextranase (PDB code 1ULV) (61), with a template modeling score of 0.8462 and root mean square deviation of 1.92 Å, indicating a good topographical match (62).…”
Section: Determination Of 2°structure Of the ␤ Subunit Within The Phkmentioning
confidence: 99%
See 1 more Smart Citation
“…The GH-15 thread coverage of ␤ is indicated in a two-color scheme, with blue and gray representing, respectively, the (␣/␣) 6 -barrel fold for the catalytic domain (A) and a mixed 2°structure corresponding to the B and C domains found in bacterial and archaeal glucoamy- lases and glucodextranases (61). The protein structurally closest to the best model of this region is Anthrobacter globiformus glucodextranase (PDB code 1ULV) (61), with a template modeling score of 0.8462 and root mean square deviation of 1.92 Å, indicating a good topographical match (62).…”
Section: Determination Of 2°structure Of the ␤ Subunit Within The Phkmentioning
confidence: 99%
“…Both cryo-EM and SAXS analyses of the native (␣␤␥␦) 4 PhK complex show it to be a large Hierarchical protein structural modeling of the ␤ subunit was carried out using I-TASSER (46). X-ray crystal structures of Aspergillus awamori glucoamylase (blue and gray ribbon traces) and human PP2A PR65/A subunit (yellow trace) were used to thread, respectively, residues 41-670 and 671-1092 of the multidomain ␤ subunit primary sequence (61,65). The remaining N-terminal residues (1-40, blue trace) were modeled ab initio using QUARK (60).…”
Section: Determination Of 2°structure Of the ␤ Subunit Within The Phkmentioning
confidence: 99%
“…In contrast, glucodextranase is defined as an enzyme that hydrolyzes the α-1,6-glucosidic linkages of dextran from the non-reducing end to produce β-glucose. We have determined the enzymatic properties and the crystal structure of A. globiformis I42 glucodextranase (7,25), and indicated that this glucodextranase hydrolyzes the α-1,4-glucosidic linkages of maltotetraose and maltose; however, their activity of glucodextranase towards α-1,4-glucosidic linkage is about 1% of that for α-1,6-glucosidic linkage. The 3-dimensional structure of glucodextranase is composed of 4 domains, N, A, B, and C (Fig.…”
Section: B Enzymes Belonging To Gh15: Glucoamylase and Glucodextranasementioning
confidence: 99%
“…Most GH15 enzymes are identified as glucoamylases, but 2 glucodextranases (EC 3.2.1.70) from Arthrobacter globiformis strains (7,23), and one trehalase (EC 3.2.1.28) from Mycobacterium smegmatis (24) belong to GH15. While glucoamylases are specific for the hydrolysis of α-1,4-glucosidic linkages, they also cleave α-1,6-glucosidic linkage; however, their activity for the α-1,6-glucosidic linkage is 0.2% of that for the α-1,4-glucosidic linkage (14).…”
Section: B Enzymes Belonging To Gh15: Glucoamylase and Glucodextranasementioning
confidence: 99%
See 1 more Smart Citation